PENDAMPINGAN TATA KELOLA ORGANISASI BAGI PENGURUS IPNU-IPPNU DI KECAMATAN BALEN KABUPATEN BOJONEGORO - Zaini Miftah; Ida Fauziatun Nisa’; M. Nasirul Umam; Sheilla Vida Rahmah; Siti Nur Vebriyanti; Ahmad Mufti Alim Arzaqi (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
Organizational governance is an important part that cannot be separated from organizational goals, because only with good governance will an organization achieve its goals well. Likewise, the governance of IPNU/IPPNU organization continues to improve its shortcomings in the hope of becoming a professional youth community organization. The important elements that are the focus of assistance in the governance of IPNU/IPPNU organization are reviewing the organizational structure, vision, mission, goals and work programs as well as the organization's articles of association and bylaws. Sustainability of this assistance in the long term according to the context, space and broader level, namely in coaching activities as long as required by the interested parties. This mentoring was attended by 30 participants from the IPNU–IPPNU Branch Management (PAC) of Balen District. After providing this assistance, it is hoped that participants will be able to design, plan, implement, evaluate and develop training in the future.